Performance and emission of turbocharger engine using gasoline and ethanol blends - S. M., Rosdi; R., Mamat; Alias, Azri; H., Hamzah; K., Sudhakar; Gholamhassan, Najafi; Farzad, Jaliliantabar (IOP Publishing, 2019)
In this decade, alternative fuels such as ethanol were extensively studied as an additive or substitute for increasing engine performance and decreasing the release of harmful gases into the environment. The objective of the study is to assess engine performance and exhaust emission using Gasoline and Ethanol blends in a turbocharged spark-ignition engine. Gasoline was used as a reference fuel, and ethanol was blended into gasoline at 10%, 20% and 30% named as E10, E20, and E30, respectively. The turbocharger spark ignition (SI) engine has been coupled to eddy current 100 kW dynamometer to measure the engine efficiency. The engine test was carried out at an engine speed of 3000 rpm and 40% wide open throttle (WOT). As results, the performance parameters such as volumetric efficiency (VE), rate of heat release (ROHR), brake mean effective pressure (BMEP), brake specific fuel consumption (BSFC) of the engine increased with gasoline-ethanol blends compared to gasoline. Also, the complete combustion contributed to the reduction of the hydrocarbon (HC), carbon dioxide (CO2) and nitrogen oxide (NOx) emissions. From the study, it can be concluded that ethanol is highly suited for turbocharged SI engines to reduce emissions and increase performance.